A Comparative Study of 25G vs 27G Quincke Needles on Incidence and Severity of Post-Dural Puncture Headache (PDPH) in Casarean Section Patients Undergoing Spinal Anaesthesia (Bangladesh Journal of Obstetrics & Gynaecology, 2026)
Background: Post-dural puncture headache (PDPH) is a common and distressing complication of spinal anaesthesia in obstetric patients. Needle gauge is a known modifiable risk factor influencing PDPH incidence and severity.Objective: To compare the incidence, severity, and perioperative characteristics of PDPH among parturients undergoing cesarean section using 25G versus 27G Quincke spinal needles.Methods: This prospective observational study was conducted at Anwar Khan Modern Medical College Hospital, Dhaka, Bangladesh, over a two-year period (January 2023–January 2025). A total of 400 patients were enrolled (200 in each group). PDPH cases were identified and analyzed for demographic, obstetric, and perioperative variables.Results: The incidence of PDPH was significantly higher in the 25G group (14%) compared to the 27G group (2%). Mild PDPH occurred in 50.0% of 27G cases vs. 3.6% in the 25G group (p = 0.0059). Although time to CSF flow was longer in the 27G group, and postoperative vomiting and vertigo were more frequent in 25G cases, these differences were not statistically significant. No significant hemodynamic changes were observed between groups.Conclusion: The 27G Quincke needle significantly reduces both the incidence and severity of PDPH without increasing procedural or clinical complications. Its adoption in obstetric spinal anaesthesia may enhance maternal outcomes and should be considered in local practice guidelines.Bangladesh J Obstet Gynaecol, 2025; Vol. 40(2): 91-100